The Emergence of Resources Seeking Chinese Firms’ Specific Advantages in Emerging Market - Ojo, Olukayode Iwaloye; Im, Hong Kei; Adeniyi, Damilola Olarewaju; Gbadamosi, Ayantunji; Alves, Jose; Link to external site, this link will open in a new window; Trimarchi, Michael (Sustainability, 2022)
It is argued that the role of the Chinese government to support the cross-border operations of Chinese firms is to assist these firms in overcoming their limited established brands, and their disadvantages in technology and managerial resources, which were also the reasons why such firms decided to enter emerging markets instead of developed markets. This strategic choice is preferred to avoid direct confrontation with established firms from developed countries endowed with superior ownership advantages. Therefore, Chinese resources seeking firms innovate by increasing investment in developing and emerging markets to develop unique ownership advantages for sustainable market development and competitive advantage. This research investigates the ownership advantages of resources seeking Chinese firms in these markets using the OLI theory. The paper contributes to explaining the specific advantages of Chinese MNEs when entering emerging markets. The study applied a two-stage qualitative methodology to examine Chinese firms operating in Nigeria. The first stage included an exploratory study based on interviews with key informants and experts while the second stage included a case study methodology. The study focused on resources seeking Chinese MNEs operating in Nigeria.
Num Pages: 8345 Place: Basel, Switzerland
Keywords: OLI theory and Chinese firms; emerging markets; ownership advantages; resources seeking MNEs